Analysis of Consumer Preferences in Buying Chicken Carcass in Sumbersari District, Jember Regency - Kusuma, Satria Budi; Subagja, Hariadi; Imam, Shokhirul (Universitas Halu Oleo, 2022)
This study aims to analyze differences in consumer preferences for buying chicken carcasses in Sumbersari District, Jember Regency, East Java. The research method uses a survey method with interviews based on a list of questions on the questionnaire. The sample was determined by the accidental sampling method with 49 samples. Sources of data used are primary and secondary data with descriptive analysis. The results of the analysis show that the largest consumer age group for chicken meat is 17-27 years old (68%), the consumer profession is dominated by students (61%), and the frequency of consumption of chicken meat is once a week (43%), the desired price of chicken is Rp18,000 - Rp20,000/kg (61%), the most preferred part of the chicken is the breast (29%), the method of ordering chicken meat is through online media (65%), the most popular side dish for chicken is poultry eggs (39%), and the most popular method of cooking chicken is by frying (76%). From the results of the study, it can be concluded that the majority of consumers are millennials who are technology literate, wanting practicality in obtaining chicken carcasses at more affordable prices.Keywords: chicken carcass, consumer, preference